1995
DOI: 10.1097/00000658-199510000-00014
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Randomized Trial of Pancreaticogastrostomy Versus Pancreaticojejunostomy After Pancreaticoduodenectomy

Abstract: ObjectiveThe authors hypothesized that pancreaticogastrostomy is safer than pancreaticojejunostomy afte pancreaticoduodenectomy and less likely to be associated with a postoperative pancreatic fistula Summary Background DataPancreatic fistula is a leading cause of morbidity and mortality after pancreaticoduodenectomy, occurring in 10% to 20% of patients. Nonrandomized reports have suggested that pancreaticogastrostomy is less likely than pancreaticojejunostomy to be associated with postoperative complications.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
442
2
23

Year Published

1998
1998
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 684 publications
(486 citation statements)
references
References 33 publications
18
442
2
23
Order By: Relevance
“…However, a recent prospective randomized trial by Yeo et al [45]was not able to support this assumption: they showed similar pancreatic fistula rates after pancreaticogastrostomy (12.3%) and pancreaticojejunostomy (11.1%), indicating that the experience of the surgeon doing the pancreaticointestinal anastomosis is of more importance than the type of reconstruction.…”
Section: Surgical Complications Following Pancreatic Resectionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, a recent prospective randomized trial by Yeo et al [45]was not able to support this assumption: they showed similar pancreatic fistula rates after pancreaticogastrostomy (12.3%) and pancreaticojejunostomy (11.1%), indicating that the experience of the surgeon doing the pancreaticointestinal anastomosis is of more importance than the type of reconstruction.…”
Section: Surgical Complications Following Pancreatic Resectionmentioning
confidence: 99%
“…Although it is not associated with higher mortality, its occurrence results in longer hospitalization [45, 50], reduced quality of life and increasing health costs. It occurs in about one third of patients after pancreaticoduodenectomy (a range of 25–70% is described in the literature) [45, 50, 74, 75, 76]. The wide range of incidence of delayed gastric emptying in several studies is probably based on different definitions of this complication.…”
Section: Surgical Complications Following Pancreatic Resectionmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation adds to the multiple reports of good experience with this anastomosis [1, 2, 3, 4, 5, 6, 7, 8, 9, 10]. However, in a prospective randomized study comparing pancreaticojejunostomy and pancreaticogastrostomy, Yeo et al [13]found no difference in the pancreatic anastomotic leak rate in their 145 patients. Pancreatic fistulas were though more common in their patient group than in other reported studies of pancreaticogastrostomy (table 1).…”
Section: Discussionmentioning
confidence: 61%
“…Ampullary tumors are localized on presentation in 78% of cases and seldom have vascular encasement or dissemination [15]. Nevertheless, patients with ampullary tumor have a soft pancreas, which is more prone to anastomotic leaking with its associated morbidity and mortality [16, 17]. …”
Section: Discussionmentioning
confidence: 99%